Meaning of life among elderly individuals with chronic diseases living with family: A qualitative study - Bahtiar, Bahtiar; Sahar, Junaiti; Wiarsih, Wiwin (UI Scholars Hub, 2020)
Background: Many elderly individuals receive lifelong treatment caused by chronic diseases with symptoms that affecting them physically, psychologically, socially, and spiritually. Spirituality plays an essential role in health conditions and social relationships given that it provides meaning to the elderly individuals life by allowing them to see the wisdom of life events experienced. This research aimed to explore the meaning of life among elderly individuals with chronic diseases. Methods: This research applied descriptive phenomenology using Colaizzi’s method of thematic analysis among 13 elderly patients with chronic diseases. Results: Elderly individuals with chronic diseases found meaning through the following items: (1) surrender to God, (2) divine destiny, (3) care until death, (4) guarantee for health finance, (5) role replacement, and (6) observing the development of children and grandchildren. Conclusion: Elderly individuals with chronic diseases can obtained positive meaning in life through family support. Families are thus expected to facilitate the development of meaning in the lives of elderly individuals with chronic diseases to help them fulfill their spiritual needs.